Profil dorosłego uczącego się języka polskiego jako obcego, czyli kto, gdzie, dlaczego i w jaki sposób uczy się języka polskiego w naszym kraju - Janowska, Iwona (Neofilolog, 2019)
The changing status and conditions of teaching Polish language in the Eu-ropean context have led to a fundamental shift in the profile of Polish lan-guage learners, their needs, motivation and learning aims. What follows is the fact that the curricula creators, course organisers and the authors of teaching materials, course books and learning aids have faced new challeng-es, problems, and learner expectations. The following paper is an attempt to outline the profile of an adult learner studying Polish in Poland.